Foreign aid and sustainable agriculture in Africa - Siddig Umbadda; Ismail Elgizouli (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2013)
Although agriculture is important for the livelihood of most Africans, especially the poor, donors did not accord it a high priority. Both volume and share of aid earmarked for agriculture in sub-Saharan Africa not only remained low, around five per cent, but continuously declined beween 1981-2001, before picking up after the world food crisis in 2007-08. Aid recently became a top agenda in donors' priorities because of concerns about its effectiveness and also because of budget pressures in donor countries as well as queries raised by their tax payers. However, despite skepticism about its effectiveness there exist successful experiences in aid supported projects that could be candidates both for scaling up and transferability across countries.
Keywords: O55; Q1; 330; agriculture; foreign aid; effectiveness; upscaling; transferability; sustainable